Combinatorial image analysis : 17th International Workshop, IWCIA 2015, Kolkata, India, November 24-27, 2015, proceedings /: 17th International Workshop, IWCIA 2015, Kolkata, India, November 24-27, 2015, proceedings. (2015) - Unknown
No abstract available